2006
DOI: 10.1111/j.1600-0560.2006.00627.x
|View full text |Cite
|
Sign up to set email alerts
|

Nestin expression in cutaneous melanomas and melanocytic nevi

Abstract: We conclude that expression of the intermediate filament protein nestin might be an indicator of tumor dedifferentiation and more aggressive behaviour. Furthermore, we suggest that nestin might be a relevant marker of tumorous and non-tumorous angiogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
71
1
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 26 publications
(25 reference statements)
7
71
1
2
Order By: Relevance
“…It is downregulated upon terminal differentation of melanocytes, and appears to be a necessary cofactor for the expression of nestin, which has been correlated with tumor progression. [43][44][45] Given this, we hypothesized that SOX10 and/or nestin may have been differentially expressed in the two subtypes; the data did not support this theory.…”
Section: Discussionmentioning
confidence: 96%
“…It is downregulated upon terminal differentation of melanocytes, and appears to be a necessary cofactor for the expression of nestin, which has been correlated with tumor progression. [43][44][45] Given this, we hypothesized that SOX10 and/or nestin may have been differentially expressed in the two subtypes; the data did not support this theory.…”
Section: Discussionmentioning
confidence: 96%
“…16 Nestin, an intermediate filament protein expressed in the cytoplasm of neuroepithelial cells and a marker for neural progenitor cells in the central nervous system, has been described as a marker of melanocytic stem cells. [11][12][13][14] Previous studies have shown that there is an increased expression of this protein in malignant vs benign nevomelanocytic proliferations and that there appears to be a stepwise increase in the proportion of lesions expressing nestin from banal nevi to primary melanomas to metastatic melanoma. 12,13 More recently, nestin staining in stage I and II melanoma patients significantly predicted poor survival with lower rates in cases with nestin positivity in both tumoral and endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…3 Nestin, an intermediate filament protein expressed in the cytoplasm of neuroepithelial cells, is known to be a marker for neural progenitor cells in the central nervous system. [11][12][13][14] Recently described as a melanocytic stem cell marker, 12 nestin has been shown to have a significantly higher expression in melanomas compared with nevi and in metastatic melanomas compared with primary melanomas. [12][13][14] The primary aim of this study was to ascertain immunohistochemical expression of the ABC transporters ABCB5 and ABCF2 and, the stem cell marker, nestin in a spectrum of benign and malignant nevomelanocytic proliferations that ranged from banal nevi to invasive primary cutaneous melanomas to assess whether they played a role in the development of malignancy.…”
mentioning
confidence: 99%
“…136 Nestin expression is associated with cell migration and metastasis in prostate cancer, 137 and tumor progression and deceased survival in melanoma. 41,[138][139][140][141][142] Nestin and SOX2, 143 an embryologic stem cell transcription factor that binds an enhancer region on the nestin gene, 144 are preferentially coexpressed in metastatic melanomas when compared with nevi or primary melanomas. 145 Moreover, SOX2-positive melanoma cells tend to be more spindleshaped cells and to have a more peripheral nestin pattern, which may represent a motile, more mesenchymal phenotype.…”
Section: How Primitive Melanoma Cells May Encourage 'Vasculogenic Mimmentioning
confidence: 99%